I had seen castles - Rylant, Cynthia (Orlando : Harcourt, 2004)
Now an old man, John is haunted by memories of enlisting to fight in World War II, a decision which forced him to face the horrors of war and changed his life forever.
Keywords: World War, 1939-1945 -- Juvenile fiction; World War, 1939-1945 -- Fiction